HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KEMAMPUAN DRIBBLING PADA KLUB SEPAKBOLA BINATAMA BENGKALIS TAHUN 2016 - Widodo, Agung; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the players club Binatama still does not have a good dribbling ability. An overly focused eye view of obstacles during dribbling causes the ball to be difficult to control end easy to lose the ball, then the ball is too far away from the food, the speed at which the ball is slowed down and the agilitiy of the ball at the ball is often missed. The purpose of this research is to know the significant correlation between agility and speed with dribbling agility at football club Binatama Bengkalis in 2016. The sample in this research is 25people by using total sampling. The instrument used are dodging run for agility, running to measure speed and dribbling ability. The data obtained were analyzed using sample and the multiple product moment correlation. Based on the results of the research that has been authors described in the previous chapter, it can be concluded as follows.: there is a correlation between agility with dribbling ability, where rtab at a significant level ? (0,05) = 0,404 means rcount (0,571) > rtab (0,404). There is a relation between speed with dribbling ability, where rtab at significant level ? (0,05) = 0,404, means rcount (0,550) > rtab (0,404). There is a mutual correlation between agility and speed with dribbling abilities at Binatama Bengkalis football club in 2016, where rtab at significant level ? (0,05) = 0,404, berarti Rcount (0,663) > rtab (0,404).Keyword: agility, speed, dribbling ability